Morphological and genetic study of the masked flying fox, Pteropus personatus; with a new subspecies description from Gag Island - Sigit Wiantoro; Ibnu Maryanto (Treubia, 2016)
The study on the specimens of Masked Flying Fox, Pteropus personatus from Gag and Moluccas Islands, Indonesia was conducted by using morphological and genetic analyses. Morphologically, the specimens from Gag are different from the other populations in Moluccas Islands by the smaller size of skull, dental and other external measurements. Based on the measurements of the specimens, the population from Gag Island is identified as P. personatus acityae n. subsp. The phylogenetic reconstruction based on partial cytochrome b sequences also support the differences between P. personatus acityae n. subsp and Pteropus personatus personatus. Thus, recently two subspecies of P. personatus are recognised from its distribution areas.